Applications of Computer Technologies in Teaching Applied Mechanics (Eurasian Journal of Engineering and Technology, 2022)
The article describes the main scientific and methodological results of new computer methods obtained in the teaching of "Applied Mechanics". A methodology has been developed for solving the tasks set in teaching "Applied Mechanics" and "Strength of Materials" based on computer learning technologies.